Mahalanobis distances on factor model based estimation - Deliang Dai (Econometrics, 2020)
A factor model based covariance matrix is used to build a new form of Mahalanobis distance. The distribution and relative properties of the new Mahalanobis distances are derived. A new type of Mahalanobis distance based on the separated part of the factor model is defined. Contamination effects of outliers detected by the new defined Mahalanobis distances are also investigated. An empirical example indicates that the new proposed separated type of Mahalanobis distances predominate the original sample Mahalanobis distance.
Keywords: 330; covariance matrix estimation; dimension reduction; multivariate analysis; outlier detection